(untitled) - Baderin, Mashood A.; Mashood A. Baderin (Oxford,New York, 2003)
This volume is a comprehensive and authoritative comparative analysis which asks whether Muslim States can comply with international human rights law whilst adhering to Islamic law. The traditional arguments on this subject are examined and responded to from both international human rights and Islamic legal perspectives. Through this analysis, it offers a clear vision of the realisation of international human rights within the application of Islamic law
Includes bibliographical references (p. [247]-272) and index
Keywords: Human rights; Civil rights; Civil rights (Islamic law)